2015
DOI: 10.1371/journal.pone.0127514
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network Model for K(λ) Retrieval and Application to Global Kpar Monitoring

Abstract: Accurate estimation of diffuse attenuation coefficients in the visible wavelengths K d(λ) from remotely sensed data is particularly challenging in global oceanic and coastal waters. The objectives of the present study are to evaluate the applicability of a semi-analytical K d(λ) retrieval model (SAKM) and Jamet’s neural network model (JNNM), and then develop a new neural network K d(λ) retrieval model (NNKM). Based on the comparison of K d(λ) predicted by these models with in situ measurements taken from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…To overcome this problem, the Hydrolight model was used to generate two synthetic data sets with SeaWiFS wavelengths in this study. First, a synthetic data set was used to refine the four‐band neural network K d (λ) algorithm (FNNK) (Chen et al, ) to improve the capability of FNNK in reducing the R rs residual error in the satellite data. This data set has 12,021 data points (see Table ), with chlorophyll‐a randomly changing from 0.01 to 15 mg m −3 , large suspended particles randomly ranging from 0.01 to 10 g m −3 , the gelbstoff absorption coefficient at 443 nm randomly ranging from 0.001 to 1.0 m −1 , both exponential slopes ( S ) associated with gelbstoff and detritus randomly fixed in the range of 0.01–0.02, and power coefficient of backscattering coefficient ( Y ) randomly fixed in the range of 0–2.…”
Section: Data Method and Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome this problem, the Hydrolight model was used to generate two synthetic data sets with SeaWiFS wavelengths in this study. First, a synthetic data set was used to refine the four‐band neural network K d (λ) algorithm (FNNK) (Chen et al, ) to improve the capability of FNNK in reducing the R rs residual error in the satellite data. This data set has 12,021 data points (see Table ), with chlorophyll‐a randomly changing from 0.01 to 15 mg m −3 , large suspended particles randomly ranging from 0.01 to 10 g m −3 , the gelbstoff absorption coefficient at 443 nm randomly ranging from 0.001 to 1.0 m −1 , both exponential slopes ( S ) associated with gelbstoff and detritus randomly fixed in the range of 0.01–0.02, and power coefficient of backscattering coefficient ( Y ) randomly fixed in the range of 0–2.…”
Section: Data Method and Techniquesmentioning
confidence: 99%
“…Chen et al () showed that the influences of R rs residual errors could be removed as long as the spectral characteristics of R rs residual errors are properly assimilated into the ocean color algorithm. In this study, the FNNK algorithm originally developed by Chen et al () is refined to obtain the vertical diffuse attenuation coefficient ( K d (λ)). Instead of single band method in the original FNNK algorithm (SFNNK) (Chen et al, ), the band difference method proposed by Chen et al () is coupled into the FNNK algorithm to minimize the impacts of R rs residual errors on K d (λ) estimations.…”
Section: Data Method and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in situ measurements of Kd(PAR) in waters have obvious limitations, and it is difficult to achieve spatial coverage. Satellite remote sensing has achieved the mapping of Kd(PAR) distribution from various types of satellite remote sensing data in open sea, coastal and inland waters in recent years (Chen & Zhu & Wu & Cui & Ishizaka & Ju, 2015;Shi et al, 2014;Song et al, 2017). However, Environmental change and anthropogenic activity have made it challenging to accurately assess Kd patterns in the extremely turbid inland waters (Zheng & Ren & Li & Huang & Liu & Du & Lyu, 2016).…”
Section: Introductionmentioning
confidence: 99%